Risk factors for low vitamin D status in Korean adolescents: the Korea National Health and Nutrition Examination Survey (KNHANES) 2008–2009. Issue 4 (6th March 2013) - Lee, Young Ah; Kim, Hwa Young; Hong, Hyunsook; Kim, Ji Young; Kwon, Hyun Jin; Shin, Choong Ho; Yang, Sei Won
Abstract Objective To evaluate the prevalence of vitamin D deficiency and predictors for low vitamin D status in Korean adolescents living between latitudes 33° and 39°N. Design A descriptive cross-sectional study. Setting Korea National Health and Nutrition Examination Survey (KNHANES) 2008–2009. Subjects A total of 1510 healthy adolescents aged 12–18 years (806 male, mean age 14·7 years) participated. Possible predictors for low vitamin D status (log-transformed 25-hydroxyvitamin D (25(OH)D) concentrations) were evaluated. Results The prevalence of vitamin D deficiency (25(OH)D<20 ng/ml) was 89·1 % in spring, 53·7 % in summer, 63·9 % in autumn and 90·5 % in winter. Winter season, older age, higher education level reached, being female, being obese, a lack of vitamin D supplementation, lower milk consumption (0–<200 ml/d) and a lack of physical activity were unadjusted predictors (all P < 0·05). Multiple linear regression analysis showed that winter season (P < 0·001), higher education level (P < 0·001) and a lack of vitamin D supplementation (P = 0·012) were independent predictors for low vitamin D status. The modifying effect of season on the association between vitamin D supplement use and vitamin D status was significant (P < 0·001). Conclusions Vitamin D deficiency was highly prevalent in Korean adolescents, especially those in higher school grades. Vitamin D supplementation may contribute to maintain a better vitamin D status with lower seasonal variation. Further studies are required to determine optimal vitamin D intakes to maintain sufficient vitamin D status for Korean adolescents.